2015
DOI: 10.1177/1534735415596425
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional T Lymphocytes Generated After Therapy With an Antitumor Gallotanin-Rich Normalized Fraction Are Related to Primary Tumor Size Reduction in a Breast Cancer Model

Abstract: Natural compounds are promising sources for anticancer therapies because of their multifunctional activity and low toxicity. Although the host immune response (IR) is clearly implicated in tumor control, the relationship between natural therapies and IR has not yet been elucidated. The present work evaluates IR induction after treatment with a gallotanninrich fraction from Caesalpinia spinosa (P2Et). Breast tumor 4T1 cells were used to evaluate antitumor properties and IR activation. Apoptosis and expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(55 citation statements)
references
References 65 publications
3
46
0
6
Order By: Relevance
“…20 However, this model did not allow us to determine the generation of tumor antigen-specific T cells. In the present study, we show that treatment with a standardized fraction obtained from a plant, confers protection against tumor growth in the B16 mouse melanoma model through DCs activation and the generation of an adaptive antigen-specific IR that increases the frequencies of CD8 + IFN- γ + T cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…20 However, this model did not allow us to determine the generation of tumor antigen-specific T cells. In the present study, we show that treatment with a standardized fraction obtained from a plant, confers protection against tumor growth in the B16 mouse melanoma model through DCs activation and the generation of an adaptive antigen-specific IR that increases the frequencies of CD8 + IFN- γ + T cells.…”
Section: Discussionmentioning
confidence: 99%
“…20 Briefly, cells were fixed with 0.25% formaldehyde for 5 min, washed and then stained with the primary anti-CRT antibody followed by the Alexa Fluor 488 secondary antibody and incubated for 30 min. The MFI of stained cells was assessed within the live gate population.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, XBP1 was recently demonstrated to impede ICD in metastatic colorectal cancer cells exposed to epidermal growth factor receptor blockers and chemotherapy (Pozzi et al, 2016). Plant-derived polyphenol fractions have also been shown to induce potent ICD and T cell-dependent anti-tumor activity in preclinical models of melanoma and breast cancer (Gomez-Cadena et al, 2016; Uruena et al, 2015), but whether ER stress response factors mediate these effects remains to be determined.…”
Section: Er Stress Responses In Tumor-associated Immune Cellsmentioning
confidence: 99%
“…destroy circulating tumor cells. [34][35][36] The tetramer detection method uses a single MHC-peptide tetramer molecule to reveal TCR expression on the surface of cytotoxic T lymphocytes, resulting in their rapid detection by flow cytometry. 37 Our tetramer results demonstrated that FSTL1 enhanced the antigen-presenting ability of DCs, which agreed with the ELISpot test results.…”
Section: Discussionmentioning
confidence: 99%